2016
DOI: 10.1371/journal.pone.0149008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monoacylglycerol Lipase Activity Decreases Glucose-Stimulated Insulin Secretion in INS-1 (832/13) Cells and Rat Islets

Abstract: Lipid signals derived from lipolysis and membrane phospholipids play an important role in glucose-stimulated insulin secretion (GSIS), though the exact secondary signals remain unclear. Previous reports have documented a stimulatory role of exogenously added mono-acyl-glycerol (MAG) on insulin secretion from cultured β-cells and islets. In this report we have determined effects of increasing intracellular MAG in the β-cell by inhibiting mono-acyl-glycerol lipase (MGL) activity, which catalyzes the final step i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The possibility that environmental impacts may lead to changes in circulating redox, is potentially an important and unrecognized form of inter-organ communication. More detailed investigations on pancreatic βcell insulin secretion support such possibilities (Corkey, 2012a,b;Berdan et al, 2016;Erion and Corkey, 2018).…”
Section: Environmental Factors Impact β-Cells and Adipocytesmentioning
confidence: 95%
See 1 more Smart Citation
“…The possibility that environmental impacts may lead to changes in circulating redox, is potentially an important and unrecognized form of inter-organ communication. More detailed investigations on pancreatic βcell insulin secretion support such possibilities (Corkey, 2012a,b;Berdan et al, 2016;Erion and Corkey, 2018).…”
Section: Environmental Factors Impact β-Cells and Adipocytesmentioning
confidence: 95%
“…MOG also increases the mitochondrial redox state and interestingly, basal insulin secretion, while ROS scavengers abrogate secretion. It was not determined precisely whether MOG or a compound derived from MOG was responsible for the increases in ROS since MOG is readily metabolized to glycerol and LC-CoA (Saadeh et al, 2012;Berdan et al, 2016).…”
Section: Mono-oleoyl Glyceride (Mog) Stimulates Basal Insulin Secretionmentioning
confidence: 99%
“…Importantly, Mgll, which encodes monoacylglycerol lipase that catalyzes the conversion of monoacylglycerides to free fatty acids and glycerol was significantly increased. Mgll is required for lipolysis and improved glucose homeostasis in mice on HFD [47, 48], an infection driven increase was validated by RT-qPCR (Figure 2L). In addition, Slc1a3, which encodes for the glutamate aspartate transporter 1 that is localized in the inner mitochondria membrane as part of the malate-aspartate shuttle and is relevant for amino acid homeostasis in adipocytes, was significantly altered in our model, and was further validated by RT-qPCR (Figure 2M).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it was shown that MAGL inhibition with URB602, which is a highly non‐specific inhibitor, was found to enhance 2‐AG levels and insulin secretion in MIN6 β‐cells and isolated human islets . In a recent study, it was argued that MAGL also regulates insulin secretion from INS‐1(832/13) cells and isolated rat islets . These authors showed that pharmacological inhibition of MAGL led to decrease, but not increase in GSIS .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it was argued that MAGL also regulates insulin secretion from INS‐1(832/13) cells and isolated rat islets . These authors showed that pharmacological inhibition of MAGL led to decrease, but not increase in GSIS . However, because of high concentrations of the inhibitors used in their study the possibility of inhibition of other lipases such as HSL that produces MAG and unspecific effects, cannot be eliminated.…”
Section: Introductionmentioning
confidence: 99%